Environmental problems and policies in Kazakhstan: Air pollution, waste and water - Lyazzat Nugumanova; Miriam Frey; Natalya Yemelina; Stanislav Yugay (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2017)
We provide a comprehensive overview of the current state of environmental governance concerning air pollution, water problems and waste generation in Kazakhstan. The overview of the environmental and institutional framework in these fields reveals that major environmental problems exist in the country. Some steps have already been taken to ensure a proper management of air, waste and water. However, more coordinated cross-sectoral actions, both on the regional and the national level, need to be undertaken to ensure a productive cooperation between state institutions, business and the society.
Keywords: O13; O44; Q53; 330; air pollution; waste generation; water usage; environmental policy; institutions; Kazakhstan